Factors contributing to the adoption of social media as a business platform among UiTM students entrepreneur / Nur Farah Afiqah Azizi - Azizi, Nur Farah Afiqah (Faculty of Business and Management, 2018)
The purpose of this research is to examine the factors contributing to the adoption of social media as a business platform among UiTM students entrepreneur. This study examine adoption of social media as a business platform with five independent variables consists of performance expectancy, perceived ease of use, social influence, perceived enjoyment and facilitating condition. The respondents were students entrepreneur in UiTM Cawangan Melaka Kampus Bandaraya Melaka. The data had been collected from 181 respondents which withdrawn from the total 311 element of population by using simple random sampling method. The method used in this study are reliability analysis, descriptive statistics, correlational analysis and multiple regression analysis by using SPSS software. Thus, Multiple Regression analysis indicates that there are significant relationship between independent variable (performance expectancy, perceived ease of use, perceived enjoyment and facilitating condition) and dependent variable (adoption of social media as a business platform). Regression analysis also reveals that facilitating condition is the most influential factors towards adoption of social media as a business platform. This research are beneficial to Small Medium Enterprise (SMEs) and students entrepreneur to improve their business their business by using social media platform. Besides, Companies Commission of Malaysia and researcher will have the knowledge and data regarding student’s entrepreneur in Malaysia. Consumers will have the advantage to gain knowledge on products sold by student’s entrepreneur in Malaysia.